Dental fluorosis in primary teeth: a study in rural schoolchildren in Shaanxi Province, China - J. P. RUAN, Z. L. WANG, Z. Q. YANG, A. BÅRDSEN, A. N. ÅSTRØM, & K. BJORV (Paediatric Dentistry, 2005)
Dental fluorosis in primary teeth is considered to be relatively rare [1] and/or less severe in comparison to dental fluorosis in the permanent dentition [2–4].